2006
DOI: 10.2522/ptj.20050036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Training on Functional Status in Patients With Prolonged Mechanical Ventilation

Abstract: The results show that a 6-week physical training program may improve limb muscle strength and ventilator-free time and thus improve functional outcomes in patients requiring PMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
2
34

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(209 citation statements)
references
References 32 publications
2
171
2
34
Order By: Relevance
“…[16][17][18][19][20][21][22] Most studies, including ours, have focused on mixed diseases, but 3 were performed on subjects with COPD alone. [16][17][18] In this severely ill subject subgroup, rehabilitation programs, physiotherapy, and inspiratory muscle training have already been shown to be safe [20][21][22] and capable of improving dyspnea, 16,17 oxygen saturation, 18 respiratory muscle strength, 16,17,19 upper and lower limb muscle strength, [17][18][19] exercise tolerance, 16,17,19,21,22 and activities of daily life functional scores, 14,20,21 and of decreasing hospital stay 16,18 and weaning time. 20 Clini et al 21 showed that most PMV subjects can benefit from a comprehensive rehabilitation program, suggesting that the degree of improvement of functional disability is associated with survival and weaning success rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] Most studies, including ours, have focused on mixed diseases, but 3 were performed on subjects with COPD alone. [16][17][18] In this severely ill subject subgroup, rehabilitation programs, physiotherapy, and inspiratory muscle training have already been shown to be safe [20][21][22] and capable of improving dyspnea, 16,17 oxygen saturation, 18 respiratory muscle strength, 16,17,19 upper and lower limb muscle strength, [17][18][19] exercise tolerance, 16,17,19,21,22 and activities of daily life functional scores, 14,20,21 and of decreasing hospital stay 16,18 and weaning time. 20 Clini et al 21 showed that most PMV subjects can benefit from a comprehensive rehabilitation program, suggesting that the degree of improvement of functional disability is associated with survival and weaning success rates.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,12 In particular, patients may receive a prompt and dedicated physiotherapy rehabilitation program in chronic ventilator facilities, 1,3,13 and transfer from an ICU to a chronic ventilator facility substantially improved patients' ambulation and activities of daily life irrespective of the underlying pathophysiology, avoiding unnecessary immobilization 14 . To date, the role of comprehensive rehabilitation in critically ill adults still remains controversial 13 or not fully established 15 : patients who have survived a recent acute respiratory failure (ARF) event can benefit from an individually tailored physiotherapy rehabilitation program that improves clinical indices, respiratory and peripheral muscle strength, activities of daily life, exercise tolerance, and disability scores. 14,[16][17][18][19][20][21][22][23][24] Once the precipitating cause of the ARF episode has been solved, these chronically ill patients still require care due to their huge motor disabilities, clinical dependence (oxygen, mechanical ventilation, nutritional, and communication device needs), and nursing necessities, 3 which the care team (physiotherapist, doctor, and nurse) must measure to better guide the daily care of the patient. No study has been performed with a large patient sample to investigate patient needs with these 3 different perspectives combined.…”
Section: Introductionmentioning
confidence: 99%
“…Use of early physical activity, delivered within 48 hours of mechanical ventilation by a mobility team consisting of nurses and physical and/or occupational therapists is shown to reduce functional dependency at hospital discharge in patients recovering from acute respiratory failure (10)(11)(12)(13)(14)(15). Early ICU activity is also associated with reductions in durations of delirium and mechanical ventilation and a trend toward decreased development of ICU-acquired weakness (15).…”
mentioning
confidence: 99%
“…In most cases, the necessity of prolonged mechanical ventilation (MV) contributes to these alterations, decreasing the functionality state and, consequently, the quality of life of these patients after hospital discharge 16 . MV is associated with increased periods of hospitalization and ICU stay, and also increased mortality [7][8][9][10][11][12][13][14]17,18 . ICUs in Brazil and worldwide have been searching for alternative therapies to help assisting patients [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Muscle dysfunction is common in mechanically ventilated ICU patients due to physical inactivity, inflammatory processes, and the use of pharmacological agents, e.g., corticosteroids, neuromuscular blocking drugs, and antibiotics [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . Neuromuscular disorders are especially common in these patients, with an average prevalence of 57% 15 .…”
Section: Introductionmentioning
confidence: 99%